Preparation method of Fe-Ni bimetallic catalyst wrapped by carbon nano tube and application of Fe-Ni bimetallic catalyst in sewage treatment

By using the Fe-Ni bimetallic catalyst wrapped in carbon nanotubes, the problem of inactivation and contamination of single-component iron-based catalysts when activated persulfate is solved, the efficient antibiotic degradation effect is achieved, and a highly efficient wastewater is provided Processing method.

CN119455951APending Publication Date: 2025-02-18LINYI UNIVERSITY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411865017.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing single-component iron-based catalysts lack electron donors when activating persulfates, resulting in inactivation, aggregation and susceptibility to metal ions, limiting their catalytic capabilities and application potential.

Method used

Using a Fe-Ni bimetallic catalyst wrapped in carbon nanotubes, FeCl3·6H2O, NiCl2·6H2O and terephthalic acid were dissolved in DMF, NaOH solution was added to heat the reaction to form MIL-88B (Fe,Ni). Then mixed with melamine for pyrolysis to obtain the Fe-Ni bimetallic catalyst M-Fe-Ni wrapped in carbon nanotubes.

Benefits of technology

The catalyst can reach a degradation rate of 99.9% in a very short time, significantly improving the catalytic performance, avoiding secondary metal pollution, and providing an efficient wastewater treatment method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455951A_ABST
    Figure CN119455951A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalyst preparation, and particularly relates to a preparation method of a Fe-Ni bimetallic catalyst wrapped by a carbon nano tube and application of the Fe-Ni bimetallic catalyst in sewage treatment. The method is realized through the following steps: firstly, dissolving ferric salt, nickel salt and terephthalic acid in a solvent, performing heating reaction after violent stirring, cooling to room temperature, collecting obtained precipitates, performing centrifugal washing, and finally performing vacuum drying to obtain MIL-88B (Fe, Ni); the preparation method comprises the following steps: uniformly mixing MIL-88B (Fe, Ni) powder with melamine, and carrying out pyrolysis to obtain M-Fe-Ni; the bimetallic catalyst (M-Fe-Ni) wrapped by the carbon nano tube prepared by the preparation method disclosed by the invention can be used for degrading organic pollutants, and after being activated by PMS, the M-Fe-Ni shows obvious Fenton-like catalytic activity for degrading the organic pollutants such as sulfamethoxazole and the like. The degradation rate of the synthesized M-Fe-Ni catalyst can reach 99.9% in an extremely short time, and is higher than the degradation efficiency of a single metal catalyst (Fe3C / Fe-coated N-C-9). Besides, due to double reaction sites of the prepared M-Fe-Ni catalyst, the migration distance between active substances and organic pollutant molecules is greatly shortened, the catalytic performance of M-Fe-Ni is remarkably improved, and degradation of organic pollutants under the condition of no secondary metal pollution is facilitated. And a potential method is provided for efficient sewage treatment of the M-Fe-Ni / PMS system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst preparation, and specifically relates to a method for preparing a Fe-Ni bimetallic catalyst wrapped by carbon nanotubes and application of the catalyst in sewage treatment. Background Art

[0002] Antibiotics are widely used to promote animal growth and protect humans from bacterial infections. Common antibiotics include fluoroquinolones, sulfonamides, tetracyclines, β-lactams and macrolides. The abuse of antibiotics can lead to large-scale outbreaks of various drug-resistant bacteria. Their parent compounds and metabolites enter the environment with medical wastewater, pharmaceutical wastewater, sewage treatment plant tailwater, livestock and poultry breeding wastewater and agricultural runoff, posing a serious threat to the ecological environment and human health. Currently, the commonly used antibiotic removal technologies include adsorption, biological treatment and chemical treatment. Advanced oxidation processes (AOPs) in chemical treatment methods produce a large number of reactive oxygen species that gradually decompose antibiotics into non-toxic, low-toxic or biodegradable small molecules. Fenton-like advanced oxidation processes based on persulfate are expected to solve the problem that the pH range of the Fenton method is not wide. Common persulfates include peroxymonosulfate (PMS) and peroxydisulfate (PDS), which are a cost-effective strategy for the oxidative degradation of antibiotics. They are activated by transition metal ions (such as iron, silver, copper, cobalt, nickel, manganese, vanadium, sodium and cerium) to produce highly reactive oxygen.

[0003] Single-component iron-based catalysts lack sufficient functional groups and active centers, and iron ions are easily deactivated, easily aggregated, and easily contaminated by metal ions. When activating persulfate, due to the lack of electron donors, the single iron element cannot be reduced, which hinders the formation of the cyclic activation process and makes it difficult to maintain a good degradation efficiency, thus limiting its catalytic ability and application potential. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a method for preparing a Fe-Ni bimetallic catalyst wrapped by carbon nanotubes.

[0005] The present invention also provides the use of the Fe-Ni bimetallic catalyst wrapped by the carbon nanotubes prepared by the above preparation method in the degradation of antibiotics in sewage.

[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: The present invention provides a method for preparing a Fe-Ni bimetallic catalyst wrapped by carbon nanotubes, comprising the following steps: (1) FeCl3·6H2O, NiCl2·6H2O and terephthalic acid (PTA) were dissolved in DMF (N,N-dimethylformamide), and NaOH solution was added. The mixed solution was stirred vigorously and then heated for reaction. After cooling to room temperature, the obtained precipitate was collected, washed by centrifugation, and finally dried in vacuum to obtain MIL-88B (Fe, Ni); (2) MIL-88B (Fe, Ni) powder and melamine are evenly mixed and pyrolyzed to obtain M-Fe-Ni.

[0007] Preferably, in step (1), the concentrations of FeCl3·6H2O and NiCl2·6H2O in the DMF solution are both 0.1-0.8 mol / L; the concentration of terephthalic acid in the DMF solution is 0.14 mol / L; and the concentration of the NaOH solution is 2 mol / L.

[0008] Preferably, in step (1), the stirring is carried out at 500-1000 rpm for 15 hours; the heating reaction is carried out at 100° C. for 12 hours; and the vacuum drying temperature is 60° C.

[0009] Preferably, in step (2), the mass ratio of the MIL-88B (Fe, Ni) powder to melamine is 1:7-20.

[0010] Preferably, in step (2), the pyrolysis is carried out under a flowing nitrogen atmosphere at 2°C min -1 The temperature was raised to 900 °C at a heating rate and pyrolysis was carried out for 4 h.

[0011] The present invention also provides a Fe-Ni bimetallic catalyst wrapped by carbon nanotubes prepared by the above preparation method.

[0012] The present invention further provides the use of the Fe-Ni bimetallic catalyst wrapped by the carbon nanotubes in the degradation and removal of antibiotics in pollutant solutions.

[0013] Preferably, when the carbon nanotube-wrapped Fe-Ni bimetallic catalyst is used for the degradation and removal of antibiotics in a pollutant solution, the steps specifically include: adding the carbon nanotube-wrapped Fe-Ni bimetallic catalyst to the pollutant solution, stirring the solution for 20 minutes, and then adding PMS.

[0014] Preferably, the concentration of the Fe-Ni bimetallic catalyst wrapped by carbon nanotubes in the pollutant solution is 0.05-0.2 g / L; the concentration of the PMS in the pollutant solution is 0.1-0.8 g / L.

[0015] Preferably, the antibiotics include but are not limited to sulfonamide antibiotics and tetracycline antibiotics.

[0016] Preferably, the sulfonamide antibiotics degraded by the carbon nanotube-wrapped Fe-Ni bimetallic catalyst provided by the present invention are sulfamethoxazole, sulfamethoxazole sodium, etc.; the tetracycline antibiotics are tetracycline, chlortetracycline, oxytetracycline, etc.

[0017] Study on the catalytic performance of M-Fe-Ni / PMS in degrading organic pollutants: The present invention uses sulfamethoxazole as the target substrate to study the catalytic performance of the M-Fe-Ni / PMS degradation system. The degradation reaction of sulfamethoxazole is carried out in the aqueous phase, and the concentration change of sulfamethoxazole is detected by high performance liquid chromatography.

[0018] The beneficial effects of the present invention are: (1) The method provided by the present invention is simple, highly operable, and the synthesized catalyst is efficient and stable; (2) The present invention provides a strategy for a carbon nanotube-wrapped Fe-Ni bimetallic catalyst, which uses heterometallic complexes with different atomic distances to achieve controllable preparation of heteronuclear bimetallic atomic pairs with different atomic distances; (3) The carbon nanotube-wrapped bimetallic catalyst (M-Fe-Ni) prepared by the present invention can be used for the degradation of organic pollutants. After activation by PMS, M-Fe-Ni exhibits obvious Fenton-like catalytic activity for the degradation of organic pollutants such as sulfamethoxazole. The degradation rate of the synthesized M-Fe-Ni catalyst can reach 99.9% in a very short time, which is higher than the degradation efficiency of the single metal catalyst (Fe3C / Fe@NC-9). In addition, the dual reaction sites of the prepared M-Fe-Ni catalyst greatly shorten the migration distance between the active substance and the organic pollutant molecules, significantly improve the catalytic performance of M-Fe-Ni, and facilitate the degradation of organic pollutants without secondary metal pollution. It provides a potential method for efficient wastewater treatment of M-Fe-Ni / PMS system. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 A flow chart for preparing M-Fe-Ni provided in an embodiment of the present invention; Figure 2 TEM image of M-Fe-Ni prepared in Example 1; Figure 3 This is the SEM image of M-Fe-Ni prepared in Example 1; Figure 4 XRD pattern of M-Fe-Ni prepared in Example 1; Figure 5 This is the EDS image of M-Fe-Ni prepared in Example 1; Figure 6The degradation efficiency diagram of sulfamethoxazole by M-Fe-Ni / PMS system at different catalyst dosages; Figure 7 This is the anti-anion interference diagram of the M-Fe-Ni / PMS degradation system; Figure 8 This is the degradation efficiency diagram of sulfamethoxazole under different catalyst degradation systems. DETAILED DESCRIPTION

[0020] The technical solution of the present invention is further explained and illustrated by means of specific embodiments below.

[0021] Unless otherwise specified, the raw materials used in the preparation process of the present invention are commercially available.

[0022] The preparation flow chart of the Fe-Ni bimetallic catalyst M-Fe-Ni wrapped by carbon nanotubes provided by the present invention is as follows Figure 1 shown.

[0023] Example 1 (1) Preparation of M-Fe-Ni: FeCl3·6H2O (1.35 g, 5 mmol), NiCl2·6H2O (1.19 g, 5 mmol) and PTA (0.58 g, 3.5 mmol) were dissolved in 25 ml DMF and sonicated until completely dissolved. 2 ml of 2 mol / L NaOH solution was added, and the mixed solution was vigorously stirred at room temperature for 15 h and then transferred to a 200 ml Teflon-lined stainless steel autoclave, heated at 100 °C for 12 h, cooled to room temperature, and the precipitate was collected, centrifuged, washed three times with DMF, and finally dried overnight in vacuum at 60 °C (the obtained powder was labeled MIL-88B (Fe, Ni)); (2) 0.1 g of MIL-88B (Fe, Ni) powder and 1.5 g of melamine powder were ground and mixed evenly, placed in a tube furnace, and pyrolyzed at 900 °C for 4 h with a heating rate of 2 °C min -1 , M-Fe-Ni was obtained by pyrolysis under flowing nitrogen.

[0024] The catalyst was characterized by TEM, SEM, XRD, EDS and XPS, which fully proved the successful preparation of M-Fe-Ni. Figure 2 , Figure 3 , Figure 4 , Figure 5It can be seen that the synthesized M-Fe-Ni has a typical nanotube structure with a size of about 200 nm. There are two broad peaks at 2ɵ=25° and 44° in the XRD spectrum, which belong to the (002) and (100) diffraction of carbon, respectively, and a broad peak at 2ɵ=51° belonging to Fe-Ni particles. It can be clearly observed in the EDS image that N, C, Fe and Ni metals are evenly distributed in the material.

[0025] Comparative Example 1 (1) Preparation of M-Fe: FeCl3·6H2O (1.35 g, 5 mmol) and PTA (0.58 g, 3.5 mmol) were dissolved in 25 ml DMF and sonicated until completely dissolved. 2 ml of 2 mol / L NaOH solution was added, and the mixed solution was vigorously stirred at room temperature for 15 h and then transferred to a 200 ml Teflon-lined stainless steel autoclave and heated at 100 °C for 12 h. After cooling to room temperature, the precipitate was collected, centrifuged, washed three times with DMF, and finally dried overnight in vacuum at 60 °C (the obtained powder was labeled MIL-88B(Fe)).

[0026] (2) MIL-88B(Fe) powder was placed in a tube furnace and pyrolyzed at 900 °C for 4 h at a heating rate of 2 °C min -1 , M-Fe was obtained by pyrolysis under flowing nitrogen.

[0027] The degradation efficiency of the M-Fe material prepared in Comparative Example 1 was 59.9% in 20 min, and the first-order kinetic rate constant was 0.0301 min -1 , which is much lower than that of M-Fe-Ni prepared in Example 1 (min -1 ).

[0028] Comparative Example 2 Preparation of M-Fe-Ni: FeCl3·6H2O (1.35 g, 5mmol), NiCl2·6H2O (1.19 g, 5mmol) and PTA (0.58 g, 3.5mmol) were dissolved in 25 ml DMF and sonicated until completely dissolved. 2 ml of 2 mol / L NaOH solution was added, and the mixed solution was vigorously stirred at room temperature for 15 h and then transferred to a 200 ml Teflon-lined stainless steel autoclave, heated at 100 °C for 12 h, cooled to room temperature, and the precipitate was collected, centrifuged, washed three times with DMF, and finally dried overnight in vacuum at 60 °C (the obtained powder was labeled MIL-88B (Fe, Ni)).

[0029] Comparative Example 3 Preparation of M-Fe: FeCl3·6H2O (1.35 g, 5 mmol) and PTA (0.58 g, 3.5 mmol) were dissolved in 25 ml DMF and sonicated until completely dissolved. 2 ml of 2 mol / L NaOH solution was added, and the mixed solution was vigorously stirred at room temperature for 15 h and then transferred to a 200 ml Teflon-lined stainless steel autoclave, heated at 100 °C for 12 h, cooled to room temperature, and the resulting precipitate was collected, centrifuged, washed three times with DMF, and finally dried overnight in vacuum at 60 °C (the resulting powder was labeled MIL-88B(Fe)).

[0030] Effect Example 1 Catalytic degradation experiments: Degradation experiments were performed in 200 mL round-bottom flasks. During this process, a thermostatic water bath was used to maintain the temperature of the reaction vessel. The initial pH of the solution was adjusted with H2SO4 (1 M) and NaOH (0.5 M). In a typical run, sulfamethoxazole solutions (100 mL) with different initial concentrations (0.02-0.1 g / L) were transferred to the round-bottom flask, and then a certain amount of catalyst (0.05-0.2 g / L) was added to the pollutant solution. The solution was stirred for 20 min to reach adsorption-desorption equilibrium. PMS (0.1-0.8 g / L) was added to start the experiment. At specific time points, 2.0 ml of the resulting solution was collected with a syringe, immediately quenched with excess methanol, and filtered through a 0.22 µm Teflon filter. The residual concentration of sulfamethoxazole in the solution was determined by HPLC. Figure 6 The figure shows the degradation efficiency of sulfamethoxazole by M-Fe-Ni / PMS system at different catalyst dosages. The PMS concentration in the system is 0.2 mmol / L, the sulfamethoxazole concentration is 20 mg / L, and the M-Fe-Ni catalyst dosage is adjusted to 0.05, 0.1, 0.15, and 0.2 g / L, respectively. The degradation efficiency of sulfamethoxazole is investigated by liquid chromatography. The study found that when the M-Fe-Ni dosage is 0.15 g / L, the degradation efficiency of sulfamethoxazole can reach 99.9% within 8 minutes, and the kinetic first-order rate constant at this time is 0.9289 min -1 Continuing to increase the amount of catalyst, the degradation efficiency did not increase significantly.

[0031] Figure 7 The M-Fe-Ni / PMS degradation system is anionic interference diagram. The study found that the M-Fe-Ni / PMS degradation system has a strong anti-anion effect on Cl - 、SO4 2- 、H2PO4 - 、NO3 - The introduction of and HA had no significant effect on the degradation efficiency of sulfamethoxazole by M-Fe-Ni / PMS.

[0032] Figure 8 The figure shows the degradation efficiency of sulfamethoxazole by different catalyst degradation systems. The catalyst dosage is 0.15g / L, and the catalyst addition amount of each group is the same; the concentration of sulfamethoxazole is 40mg / L, and the concentration of PMS is 0.2mM. The results show that among the catalytic degradation systems shown, the M-Fe-Ni / PMS degradation system has the best degradation effect on sulfamethoxazole.

Claims

1. A method for preparing a Fe-Ni bimetallic catalyst wrapped by carbon nanotubes, characterized in that: The following steps are involved: (1) FeCl3·6H2O, NiCl2·6H2O and terephthalic acid were dissolved in DMF, NaOH solution was added, the mixed solution was vigorously stirred and heated for reaction, after cooling to room temperature, the obtained precipitate was collected, centrifuged and washed, and finally vacuum dried to obtain MIL-88B (Fe, Ni); (2) MIL-88B (Fe, Ni) powder and melamine are evenly mixed and pyrolyzed to obtain M-Fe-Ni.

2. The preparation method according to claim 1, characterized in that: In step (1), the concentrations of FeCl3·6H2O and NiCl2·6H2O in the DMF solution are both 0.1-0.8 mol / L; the concentration of terephthalic acid in the DMF solution is 0.14 mol / L; and the concentration of the NaOH solution is 2 mol / L.

3. The preparation method according to claim 1 or 2, characterized in that: In step (1), the stirring is carried out at 500-1000 rpm for 15 hours; the heating reaction is carried out at 100° C. for 12 hours; and the vacuum drying temperature is 60° C.

4. The preparation method according to any one of claims 1 to 3, characterized in that In step (2), the mass ratio of the MIL-88B (Fe, Ni) powder to melamine is 1:7-20.

5. The preparation method according to claim 1 or 4, characterized in that: The pyrolysis was carried out under a flowing nitrogen atmosphere at 2°C min -1 The temperature was raised to 900 °C at a heating rate and pyrolysis was carried out for 4 h.

6. A Fe-Ni bimetallic catalyst wrapped by carbon nanotubes prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the Fe-Ni bimetallic catalyst wrapped by carbon nanotubes as claimed in claim 6 in the degradation and removal of antibiotics in pollutant solutions.

8. The use according to claim 7, characterized in that: The method comprises the following steps: adding Fe-Ni bimetallic catalyst wrapped by carbon nanotubes into the pollutant solution, stirring the solution for 20 minutes, and then adding PMS.

9. The use according to claim 8, characterized in that: The concentration of the Fe-Ni bimetallic catalyst wrapped by carbon nanotubes in the pollutant solution is 0.05-0.2 g / L; the concentration of the PMS in the pollutant solution is 0.1-0.8 g / L.

10. The use according to any one of claims 7 to 9, characterized in that: The antibiotics include but are not limited to sulfonamide antibiotics and tetracycline antibiotics.

Citation Information

Cited By

  • Synthesis method of bimetallic catalyst with adjustable active sites

    CN121715206A

  • Iron / nickel bimetallic aminated multi-walled carbon nanotube for adsorbing sulfonamide antibiotics, and preparation method and application of iron / nickel bimetallic aminated multi-walled carbon nanotube

    CN122479719A